2015
DOI: 10.1634/theoncologist.2015-0168
|View full text |Cite
|
Sign up to set email alerts
|

Patient Attitudes Regarding the Cost of Illness in Cancer Care

Abstract: Background and Purpose. The cost of illness in cancer care and the subsequent distress has attracted scrutiny. Guidelines recommend enhanced discussion of costs, assuming this will reduce both stress and costs. Little is known about patient attitudes about cost considerations influencing treatment decisions. Methods. A convenience-sample survey of patients currently receiving radiation and/or intravenous chemotherapy at an outpatient cancer center was performed. Assessments included prevalence and extent of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 29 publications
2
55
1
Order By: Relevance
“…Twelve papers from 10 distinct studies investigated patient attitude regarding cost communication 10, 13-23 (Table 1, Supplemental Table 2). Nearly all studies took place in the US, except for an Australian study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve papers from 10 distinct studies investigated patient attitude regarding cost communication 10, 13-23 (Table 1, Supplemental Table 2). Nearly all studies took place in the US, except for an Australian study.…”
Section: Resultsmentioning
confidence: 99%
“…10, 13, 14, 17-19, 22, 23 The mean (weighted) and median of the proportion of patients who were surveyed or interviewed and expressed a positive attitude toward cost discussions was 60% and 61%, respectively, and the range was 20% 23 to 96% 22 . Of those, six reported that more than half of study participants were in favor of cost communication.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations